The girl with no nose - Georgia Byng (Edinburgh: Conkers, 2016)
Alice Peasbody was born with no nose. People laugh and jeer at Alice and call her 'Pancake Face'. Even when she is given a prosthetic nose and gains the courage to move to the big city and take an office job, she cowers in dark corners. The only place she feels she can truly be herself is the roof garden of the office block. But one day a handsome and good-natured man comes to work in Alice's office, and she finds herself drawn out of the dark corners
Keywords: Children's stories